Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/cm991043l
|View full text |Cite
|
Sign up to set email alerts
|

Polar Growth and Directional Adsorption of Large AlPO4-5 Crystals Determined by Scanning Pyroelectric Microscopy

Abstract: Scanning pyroelectric microscopy on large crystals reveals the three-dimensional polarization distribution in AlPO 4 -5 crystals. AlPO 4 -5 probably grows in such a way that one particular absolute configuration is formed. In general twinned crystals are formed. The twin domains exhibit an opposite polarization. A single domain is found when crystals are grown from a substrate. In some cases the crystals show a more complex domain structure, which can be attributed to specific growth conditions. From the polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
(31 reference statements)
6
26
0
Order By: Relevance
“…Intergrowth effects similar to those shown in Fig. 1(c) were frequently observed in other AFI-type crystals synthesized in solution (Girnus et al, 1994;Klap et al, 1999Klap et al, , 2000. For some of these crystals it was shown that only the internal crystal components, which resemble geometrically the semi-pyramids in Fig.…”
Section: Resultssupporting
confidence: 81%
“…Intergrowth effects similar to those shown in Fig. 1(c) were frequently observed in other AFI-type crystals synthesized in solution (Girnus et al, 1994;Klap et al, 1999Klap et al, , 2000. For some of these crystals it was shown that only the internal crystal components, which resemble geometrically the semi-pyramids in Fig.…”
Section: Resultssupporting
confidence: 81%
“…Klap et al have shown in a series of papers [24][25][26] that the Al À O À P vector (of the T À O À T bonds parallel to c) always points in the same direction (in fact, AFI crystal growth only takes place in that direction), thus giving a permanent polarisation to the crystal along the c direction. This macroscopic polarisation may cause the alignment of the water molecules in the 6-MR channels.…”
Section: Resultsmentioning
confidence: 99%
“…The observed commonality is in line with the assumption that the synthesis starts from rapid growth along one direction (usually crystallographic c axis), resulting in a dumbbell-shaped crystal, observed at the early stages of the synthesis. [26] The gap around the center of the crystal is subsequently filled up to form a regular shape. It was proposed that a secondary nucleation process occurs at the interface between the central and outward structures, making the boundary between them defect-rich.…”
mentioning
confidence: 99%